Физические поля, формируемые системой цилиндрических пьезокерамических излучателей с продольным пьезоэффектом - Дидусенко, Ю.А. (Технічна електродинаміка, 2012)
The analytical relationships describing the physical fields generated by the system of arbitrary parallel circular cylindrical piezoceramic radiators with longitudinal piezoelectric effect have been taken. Each of transducers is thin-walled piezoceramic multicellular cylinder performing pulsating vibrations. Physical statement of the problem and its mathematical model, which considering several types of interaction, namely, radiators’ interaction on the sound field caused by multiple scattering waves, the interaction of an electroelastic solid with the medium, interaction of acoustic, mechanical and electrical fields in each of the transducers as a result of energy conversion in the longitudinal piezoelectric effect are formulated.